1998
DOI: 10.1063/1.366676
|View full text |Cite
|
Sign up to set email alerts
|

Stress relaxation and misfit dislocation nucleation in the growth of misfitting films: A molecular dynamics simulation study

Abstract: The low-temperature growth and relaxation of misfitting films are analyzed on the basis of two-dimensional molecular dynamics simulations using Lennard-Jones potentials. The temporal evolution of the surface morphology and the mechanisms for misfit dislocation nucleation and stress relaxation are monitored. Pseudomorphic film growth is observed up to a critical thickness. In some cases, the formation of voids within the film relaxes some of the stress. At the critical thickness, dislocations nucleate and relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
72
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 40 publications
6
72
0
Order By: Relevance
“…This difference in relaxation behavior is rationalized in terms of the local anharmonic atomic potentials and difference in the dislocation nucleation mechanism for the two different strain states. 35 Fig . 4 shows the calculated critical thickness for crack formation 31 and for dislocation formation, 35 as well as our experimentally deduced layer thickness versus the misfit.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This difference in relaxation behavior is rationalized in terms of the local anharmonic atomic potentials and difference in the dislocation nucleation mechanism for the two different strain states. 35 Fig . 4 shows the calculated critical thickness for crack formation 31 and for dislocation formation, 35 as well as our experimentally deduced layer thickness versus the misfit.…”
Section: Resultsmentioning
confidence: 99%
“…The blue and red dotted lines are calculated by energy minimization method with LennardJones potential, while the black dotted line by numerically solving the energyequilibrium model by Matthews and Blakeslee. 35 The solid and hollow data points represent the experimentally measured layer thickness for crack-free and cracked samples, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 -20 Thus, atomistic studies are important for a detailed understanding and determination of the possible mechanisms for defect nucleation in epitaxial films. Although the importance of kinetic factors in real experiments has already been emphasized 11 and also investigated in numerical simulations of atomistic models of the growth process, 20 a direct determination of the transition path and corresponding energy barrier for misfit dislocation nucleation from an epitaxial film has been much less explored, and they often require assumptions on the particular structure of the intermediate configuration. 21 The actual stress relaxation processes starting from the epitaxial coherent state can occur along many different transition paths.…”
Section: Introductionmentioning
confidence: 99%
“…It is theoretically challenging to address both plasticity and buckling in this nonequilibrium process; the former involves singular contributions to the strain, while the latter constitutes a freeboundary-value problem. A molecular dynamics study of Dong et al 13 addressed both aspects of the process and found a qualitative coupling between buckling and dislocation nucleation; the relaxation of misfit strain by dislocations occurred inside grooves, which came about by the relaxation of strain by buckling. Schwarz 14 studied misfit dislocation lines in three-dimensional static films in a quasiequilibrium framework.…”
mentioning
confidence: 99%